Para athlete activism: A qualitative examination of disability activism through Paralympic sport in Ireland - Haslett, D.; Choi, I.; Smith, B. (Psychology of Sport and Exercise, 2020)
Objectives: Little attention has been given to how Para athletes use their platforms for disability activism. This paper fills this gap by examining how Irish Para athletes take actions to create social change around disability.